Encyclopedia británica, micropedia VOL. 2 / William Benton - Benton, Britannica (Estados Unidos de América: Encycloepdia Britannica, Inc, 1968)
Cross references appar often, identified by see, see also, or as related entres and always refer to other entries in the ready reference; entries are alphabetized as if they were one word up to the comme, regardless of the number of words in the title, thus; direction of index; volume and page numbers immediately following the title of an entry always refer to a comprehensive article in volumes 1 through 9.
Ilustración, tabla, mapa
Col. Ref
Keywords: 1. ENCYCLOPEDIA 2. ENCYCLOEPDIA BRITANNICA-MICROPEDIA VOL. 2 3. REFERENCE